Report on AICCRA Ethiopia Inception Workshop - Auma, Joseph (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Agriculture has remained central to the livelihoods of millions of Africans. Yet, far too many agriculture-dependent Africans remain food insecure and malnourished. Agriculture is vulnerable to climate shocks. The number of undernourished people rose from 195 million in 2006 to 256 million in 2018. By the end of 2018, more than 65 million people across 33 African countries faced "crisis" levels of acute food insecurity or worse. The COVID-19 crisis is expected to worsen food insecurity in the region further, making resilience-building an even more urgent task. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), in partnership with other CGIAR centers and with support from the World Bank, has developed an initiative to Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA). AICCRA aims to enhance access to knowledge, technologies, and practices to build the resilience of agriculture and food systems in the face of climate change in selected Sub-Saharan Africa (SSA) countries. AICCRA offers a unique opportunity to mobilize science and innovation for the benefit of agricultural development in SSA with a focus on climate information services (CIS), climate-informed digital agro-advisories and decision support tools (DSTs), climate-smart agriculture (CSA) for crop and livestock systems, including the enabling institutions and policies. By taking to scale actionable CIS and CSA technologies and practices, AICCRA strives to strengthen the productivity and resilience of agriculture in three key agro-ecological zones: Western Africa and Sahelian drylands (Ghana, Senegal, and Mali), Eastern Africa drylands, and the lowlands (Ethiopia and Kenya) to highlands and Southern Africa drylands (Zambia).